Ação de corticoides na fase aguda da neurocisticercose: nota preliminar - Guilberto Minguetti; Marlus V. C. Ferreira (Arquivos de Neuro-Psiquiatria)
Neurocysticercosis is a major public health problem in the developing countries. Previous to the CT scan era its diagnosis was very restricted and conventional diagnostic methods were unreliable. It was also frequently necessary to submit patients to costly and dangerous surgical procedures to confirm the precise nature of the disease. The most striking type of neurocysticercosis diagnosed by CT is the acute or edematous type (Table 1). Patients with this type of neurocysticercosis are referred for examination with intracranial hypertension, in general with suspicion of space-occupying lesion. In the authors' experience it is possible to obtain a dramatic reduction of the brain edema in the acute stages of neurocysticercosis using corticosteroids, the use of which completely changes the clinical picture and the CT images.